2021
DOI: 10.3390/agriculture11100974
|View full text |Cite
|
Sign up to set email alerts
|

The Value Chain of Locally Grown Japonica Rice in Mwea, Kenya

Abstract: In Kenya, there is an urgent need to strengthen domestic rice production to improve food security. To achieve this, it is necessary to develop a value chain of competitive rice varieties that creates new value over and above that of conventional varieties. In this study, we focused on locally grown japonica rice produced in the Mwea area, which has recently begun to be distributed in Nairobi. Through interviews with Japanese restaurants, Japanese food stores, and consumers as well as interviews with stakeholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This result is similar to the economic analysis of the rice value chain in India by Pavithra et al (2018), where they found millers to be the highest and most important value adder in the chain; rice millers added value in three stages of purchasing paddy, milling of the paddy and selling of white rice. These stages align with the findings of Watanabe et al (2021) in their study on the value-added ratio at the processing stage highest for the value chain of locally grown japonica rice in Mwea, Kenya.…”
Section: Unit Benefit and Value Share Of Actors Along The Chainsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is similar to the economic analysis of the rice value chain in India by Pavithra et al (2018), where they found millers to be the highest and most important value adder in the chain; rice millers added value in three stages of purchasing paddy, milling of the paddy and selling of white rice. These stages align with the findings of Watanabe et al (2021) in their study on the value-added ratio at the processing stage highest for the value chain of locally grown japonica rice in Mwea, Kenya.…”
Section: Unit Benefit and Value Share Of Actors Along The Chainsupporting
confidence: 87%
“…Currently, in Sub-Saharan Africa (SSA), rice is the second largest source of caloric intake after maize. It is expected that demand for rice will increase continuously given the shift in consumer preference in favour of rice, and the high rate of population growth in the region (Tsujimoto et al, 2019;Gebre et al, 2020;Watanabe et al, 2021). From this perspective, rice is SSA's most essential strategic crop for food and nutrition security.…”
Section: Introductionmentioning
confidence: 99%
“…Rice accounts for approximately 65% of China's food consumption, meeting the basic survival needs of its population [5,6]. However, due to population growth, social development, and climate change, improving the unit yield of rice has become a key focus of rice production research [7][8][9]. China has always adhered to the strategy of grain storage and the adoption of new agricultural technology to ensure national food security [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%